Multi-Factor Evaluation of Deep Karst Dolomite Reservoir Based on Paleogeomorphological Reconstruction, a Case Study From the 4th Member of the Dengying Formation in the Central Sichuan Basin, China - Zhou, Zikun; Wang, Xingzhi; Yang, Xiyan; Wen, Long; Wang, Wenzhi; Zeng, Deming; Wei, Mingyang; Xie, Shengyang; Huo, Fei (Frontiers in Earth Science, 2022)
The evaluation of reservoirs is of great importance in exploration practices, distribution of which is subjected to multiple geological factors. The carbonate platform of the 4th member of the Dengying Formation (Deng Ⅳ member) in the Gaoshiti-Moxi area (GMA), was uplifted above sea level during the episode Ⅱ of Tongwan Movement and underwent prolonged karstification by meteoric freshwater in the terminal Sinian, leading to a strong heterogeneity in reservoirs. Paleogeomorphic relief reflects hydraulic gradients that affect intensities of surface karstification to an extent, and the hydraulic gradients can be approximated by terrain slope gradients. Karst products (especially solution vugs and caverns) exist prevailingly in the Deng Ⅳ member, development of which mirrors internal dissolution intensities. Based on paleogeomorphological reconstruction in elevation method, the slope angles of single boreholes are calculated through digital elevation model (DEM). In accordance with single-borewell formation microscanner image (FMI) logging data, four electrofacies (viz. host rock, vug, fracture and cave) were identified in boreholes possessing FMI data. Matching the identified electrofacies with corresponding conventional logging curves as the training data, a model generalized for other boreholes without FMI data is established employing random forest algorithm, and thicknesses of the four electrofacies in each borehole are obtained to characterize the karstification intensity. Slope gradients and electrofacies thicknesses, together with multiple physical parameters depicting reservoirs in boreholes, are utilized for factor analysis. Four factors were obtained and fused into one comprehensive score in the light of their ratios of variance proportions. The favorability of reservoirs is described with the comprehensive scores of each borehole. It turns out that the most advantageous reservoirs are distributed in the vicinity of the platform margin in the west of the GMA, at which superimposition of several advantage factors may account for this. Deposition of porous mound-shoal complexes erect majorly in the platform margin where large scale caves are more developed in the mixing karst zone of seawater and freshwater, and transmeridional lateral migration of hydrocarbons from regional hydrocarbon-generating centre abutting the west of the GMA, contributing to earlier entrapment and accumulation in the mound-shoal complexes in the platform margin.